2020
DOI: 10.3389/fphar.2020.01173
|View full text |Cite
|
Sign up to set email alerts
|

Hederagenin Attenuates Cerebral Ischaemia/Reperfusion Injury by Regulating MLK3 Signalling

Abstract: Cerebral ischaemia/reperfusion (CI/R) injury is a major challenge due to the lack of effective neuroprotective drugs. Hederagenin (HE) is the aglycone part of saponins extracted from Hedera helix Linné that has exhibited anti-apoptotic and anti-inflammatory effects; however, the role of HE in CI/R has not been elucidated. In this study, mice were intraperitoneally (i.p.) injected with HE (26.5, 53, or 106 μmol/kg body weight) for 3 days after middle cerebral artery occlusion (MCAO). Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Hederagenin, as a naturally occurring triterpene, induces (drug-resistant head and neck cancer (HNC) cell apoptosis) resistant HNC cell death through the Nrf2-ARE antioxidant pathway [ 41 ]. In animal models of cerebral ischemia/reperfusion injury, hederagenin exerts antiapoptotic and anti-inflammatory effects through the MAPK and NF κ B pathways [ 42 ]. Formononetin has antioxidant and neuroprotective effects [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hederagenin, as a naturally occurring triterpene, induces (drug-resistant head and neck cancer (HNC) cell apoptosis) resistant HNC cell death through the Nrf2-ARE antioxidant pathway [ 41 ]. In animal models of cerebral ischemia/reperfusion injury, hederagenin exerts antiapoptotic and anti-inflammatory effects through the MAPK and NF κ B pathways [ 42 ]. Formononetin has antioxidant and neuroprotective effects [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is a vital pathophysiological mechanism associated with I/R, and reperfusion could accelerate the apoptotic death process induced by ischaemia (Villa et al 2003). Compelling findings indicate the inhibition of apoptosis as a key protective mechanism against cerebral I/R injury (Baldrati et al 2020;Yu et al 2020). Wen et al (2019) demonstrated that N-Myc downstream-regulated gene 4 (NDRG4) protected cerebral IR injury by inhibiting cell apoptosis and regulated cerebral cell apoptosis by increasing BDNF expression.…”
Section: Discussionmentioning
confidence: 99%
“…ED also stabilized ABCA1, a key transporter for cholesterol efflux, in THP-1-derived human macrophages [ 144 ]. Yu et al reported that intraperitoneal injection of HG attenuated cerebral ischemia/reperfusion-induced apoptosis and inflammatory cytokine expression and reduced cerebral infarction via the MLK3 signaling pathway [ 145 ]. HG also reduced bleomycin-induced pulmonary fibrosis in rats by decreasing the levels of α-SMA, collagen I, hydroxyproline, and decreased inflammatory cytokines (TNF-α and IL-6) as well as phosphorylation of JNK and NFAT4 in a dose-dependent manner [ 146 ].…”
Section: Biological Effects Of Naturally Occurring Analogues Of Uamentioning
confidence: 99%